علاقة الإتصال التنظيمي بالرضا الوظيفي - عربية، الحسين (جامعة الوادي university of Eloued, 2017)
Summary: The present study aimed to identify the relationship between "organizational communication and job satisfaction", from the general question that was drafted to the following: Is there a correlation relationship with significant satistically between organizational communication and job satisfaction at the university teacher ? however we have other following sub-questions: 1- Is there a correlation relationship with statistically significant between formal communication and job satisfaction at the university teacher ? 2 - Is there a statistically significant relationship between informal communication and job satisfaction؟ This study was based on a descriptive approach as well as the use of the questionnaire in collecting data from the field, which included (50) items and distributed in two axes. This tool was applied to a random sample of 120 individuals who are professors in the Faculty of Social and Human Sciences, Year 2016/2017. This study resulted the following: •There is a relationship between organizational communication and job satisfaction at university teacher •There is a relationship between formal communication and job satisfaction at university teacher •There is a relationship between informal communication and job satisfaction at university teacherI
دراسة ميدانية على عينة من اساتذة بكلية العلوم الاجتماعية والإنسانية
مذكرة ماستر علوم اجتماعية تخصص تنظيم وعمل
Keywords: الإتصال التنظيمي، الرضا الوظيفي; Communication organisationnelle, satisfaction au travail; Organizational communication, job satisfaction